ASJO 2022
DOI: 10.1055/s-0042-1744448
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Potential of MicroRNAs in Glioma Patients: A Meta-Analysis

Abstract: Introduction MicroRNAs are a noncoding RNA involved in affecting several transcription and translation pathways. Their use has been discussed as potential predictors of several tumors. Their use as potential biomarker in glioma patients is still controversial. The purpose of this meta-analysis is to explore the possible role of such microRNAs in glioma patients. Methods After an extensive literature search done on PubMed and Embase, 20 studies were chosen for our analyses with the 9 discussing 11 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…Consistent to the present OS, PFS, and DFS analysis, a recent meta-analysis on prognostic value of miRNAs in glioma, affirmed that both overexpression of tumor promoting miRNAs and lower expression of suppressors, are significantly associated with poor prognosis in glioma (79). 11,518 cases of glioma, included in the resent study, showed OS HRs more than one (OS HR: 2.0221 (95% CI: 1.8497-2.2105, p < 0.0001; I 2 = 74.1%)).…”
Section: Prognostic Valuesupporting
confidence: 88%
“…Consistent to the present OS, PFS, and DFS analysis, a recent meta-analysis on prognostic value of miRNAs in glioma, affirmed that both overexpression of tumor promoting miRNAs and lower expression of suppressors, are significantly associated with poor prognosis in glioma (79). 11,518 cases of glioma, included in the resent study, showed OS HRs more than one (OS HR: 2.0221 (95% CI: 1.8497-2.2105, p < 0.0001; I 2 = 74.1%)).…”
Section: Prognostic Valuesupporting
confidence: 88%